Penggunaan Media Sosial Sebagai Alat Komunikasi Politik - Sukma Alam (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
The development of increasingly sophisticated communication technology is a challenge for political parties in communication. Social media offers benefits for political parties to communicate political to the wider public. This research is to see the use of social media as political communication by DPW PSI Jakarta. This research uses a case study with observation and interviews with the social media admin of DPW PSI Jakarta and the Chairman of DPW PSI Jakarta. The results of this study indicate that the use of social media as political communication by the DPW PSI Jakarta is very helpful in the process of political communication such as influencing the public, absorbing aspirations, two-way communication and clearer and more effective communication messages.